Peranan Sultan Muhammad Ali Muazzammsyah dalam Mendirikan Kota Pekanbaru (1765-1779) - Dina Zamzarina; Bunari Bunari; Asyrul Fikri (CHRONOLOGIA, 2022)
The name Pekanbaru was formerly known as Senapelan. The development of Senapelan is very close to the Kingdom of Siak Sri Indrapura. The Siak Kingdom is a religious kingdom which is a continuation of the Johor Kingdom which was split into two regions, one of which is the Siak Kingdom which was founded by Sultan Jalil Rachmad Syah who is known as Raja Kecik. The existence of Pekanbaru City (the capital of Riau Province) cannot be separated from the role of Sultan Muhammad Ali Abdul Jalil Muazzamsyah who holds the title of Marhum Pekan in establishing this city. From a simple village (Kebatinan Senapelan) to become the capital of the Kingdom of Siak and is now a Metropolitan city. During Sultan Muhammad Ali leading the Kingdom of Siak, he built Negeri Senapelan and gave the city a new name Pekanbaru. To find out the background of Sultan Muhammad Ali Muazzamsyah's life and to know the role of Sultan Muhammad Ali Muazzamsyah in establishing Pekanbaru, making Senapelan a trading center. This research is research that seeks to reconstruct the Role of Sultan Muhammad Ali Muazzamsyah in Establishing the City of Pekanbaru (1765-1779) considering that events occurred in the past, the method used is the historical method with steps namely Heuristics, Verification, Interpretation and historiography. The result of this research is to reconstruct the role of Sultan Muhammad Ali Muazzamsyah in order to make Senapelan a trading center.